Endomorphin-2 Decreases Excitatory Synaptic Transmission in the Spinal Ventral Horn of the Rat - Wu, Zhen-Yu; Lu, Ya-Cheng; Feng, Ban; Chen, Ying-Biao; Bai, Yang; Zhang, Ting; Zhang, Hua; Chen, Tao; Dong, Yu-Ling; Li, Hui; Li, Yun-Qing (Frontiers in Neural Circuits, 2017)
Motor impairment is one of the serious side-effects of morphine, which is an exogenous agonist of the μ opioid receptor (MOR) as well as a widely-used analgesic drug in clinical practice for chronic pain treatment. Endomorphins (EMs, including EM-1 and EM-2), the most effective and specific endogenous agonists of the MOR, exert more potent analgesia in acute and neuropathic pain than other opiates, such as morphine. Although EMs had fewer side-effects comparing to other opiates, motor impairment was still one unwanted reaction which limited its clinical application. In order to prevent and treat the motor impairment, it is critical to reveal the neural mechanisms underlying such locomotion disorder. The purpose of the present study was to reveal the neural mechanisms underlying the effects of endomorphin-2 (EM-2) on the activity of motoneurons in the spinal ventral horn. First, we examine the distribution of EM-2-immunoreactive (IR) primary afferent fibers and their synaptic connections with the motoneurons innervating the skeletal muscles of the lower limb revealed by sciatic nerve retrograde tracing. The results showed that EM-2-IR fibers and terminals were sparsely observed in lamina IX and they formed symmetric synaptic connections with the motoneurons within lamina IX of the spinal ventral horn. Then, whole-cell patch-clamp technique was used to observe the effects of EM-2 on the spontaneous excitatory postsynaptic current (sEPSC) of motoneurons in lamina IX. The results showed that EM-2 could decrease both the frequency and amplitude of the sEPSC of the motoneurons in lamina IX, which was reversed by the MOR antagonist CTOP. These results indicate that EM-2-IR fibers originated from primary afferent fibers form symmetric synaptic connections with motoneurons innervating skeletal muscles of the lower limbs in lamina IX of the spinal ventral horn and EM-2 might exert inhibitory effects on the activities of these motoneurons through both presynaptic and postsynaptic mechanisms.